Empowerment and assistance of Unissula Virtual Homecare (UVHC) volunteers to increase resilience of Covid-19 patients post self-isolation - Indah Sri Wahyuningsih; Erna Melastuti; Asih Puji Lestari (Universitas Muhammadiyah Magelang, 2022)
Prevention and treatment of Covid-19 patients has been carried out with various strategies. Educational strategies can be carried out on patients during self-isolation or after self-isolation. Unissula initiated the Unissula Virtual home care innovation, namely UVHC as an effort to contribute to higher education during the pandemic. The UVHC program needs to be supported by volunteers who can assist Covid-19 patients in increasing their resilience to the problems experienced after Covid-19 so that conditions do not occur again. Assistance and empowerment of UVHC Volunteers aims to increase knowledge, skills and abilities in managing Covid-19 patients after self-isolation. This activity is carried out with training and demonstrations. After the activity, UVHC volunteers increased their knowledge of nutritional needs by 70%, skills in breathing exercises increased to 80%, knowledge of pharmacology needs to 70% and volunteer skills increased by 80% in teaching prayer procedures during illness as an effort to fulfill spiritual needs. The Service Team recommends the formation of volunteers in other fields to increase volunteer awareness in helping the healing process of Covid-19 patients after self isolation